Вы находитесь на странице: 1из 8

Math 2120 - Analysis and Mathematical Methods I Semester 1, Academic Year 2012/2013 FIRST COURSEWORK EXAM (15%) Monday 8th October 2012 Please write your student ID number AND your name on your answer booklet Instructions to Candidates: Answer any two questions Time Limit: 1 hour SOLUTIONS

(a)

(b)

Provide a formal deÖnition for the limit of a sequence. Use this deÖnition to

prove that the sequence 3n 2n + + 4 3 ; n 1

[8 marks]

2

3 :

converges to a limit

SOLUTION: The sequence f a n g n=1 converges to a limit L if given any > 0; there exists a N (positive integer) such that ja n L j < for n > N:

SOLUTION: We wish to prove that given any > 0 ; there exists a N (positive

integer) such that

Consider

1

2n + 3 3n + 4 3 2

< for n > N:

2n + 3 3n + 4 3 2

=

<

3 (2n + 3) 2 (3n + 4) 3 (3n + 4)

1

=

9n <

1

9N = for n > N

1

3 (3n + 4)

Hence for any > 0; there exists a N = 1 such that

9

2n + 3 3n + 4 3 2

< for n > N:

Consider the sequence of positive terms f a n g ; n 1 deÖned as

a 1 = 1;

a n+1 = 4 + 3a n ; n 3 + 2a n

1:

1. Use mathematical induction to prove that the sequence is increasing. SOLUTION: We need to prove that a n+1 a n 0 for all n 1:

Case n = 1; we get

a 2 a 1 = 4 + 3a 1 1 = 7 1 > 0

3 + 2a 1

5

1

hence it is true for n = 1: Assume that it is true for n = k; i.e. that

a k +1 a k 0 for all k 1:

Consider n = k + 1;

This simpliÖes to

a k +2 a k +1 = 4 + 3a k +1

3 + 2a k +1

4 + 3a k

3 + 2a k

a k +2 a k +1 =

a k +1 a k

(3 + 2a k +1 ) (3 + 2a k )

Now since we know that a k > 0 for all k since this is a sequence of positive terms, as we have that a k +1 a k 0 for all k 1; it follows that

a k +2 a k +1

0

and therefore by mathematical induction, we can conclude that a n+1 a n 0 for all n 1:

2. Use mathematical induction to prove that the sequence is bounded above by

3

2 :

SOLUTION: We need to prove that a n 3 0 for all n 1: Consider the

case n = 1; we have

a 1 3 = 1 3 < 0

2

2

2

hence it is true for n = 1: Assume it is true for n = k; i.e. that

a k 3 0 for all k 1

2

Consider the case n = k + 1; i.e.

a k +1 3

2

= 4 + 3a k

3 + 2a k

3

2

= 8 + 6a k 9 6a k

2 (3 + 2a k )

=

1

2 (3 + 2a k )

However, we know that all the terms of this sequence are positive, which means

a k +1 3

2

< 0

and therefore the case n = k + 1 is true, and by mathematical induction, we

have that a n 3 0 for all n 1:

2

2

3. Find the supremum of the sequence, justifying your answer completely. SOLUTION: By the increasing sequence theorem, this sequence is convergent to a limit L which is equivalent to the supremum. Therefore

L = lim

n!1 a n = lim

n!1 a n+1

Taking the limit of a n+1 = 4+3a n as n ! 1; we obtain

3+2a n

L

= 4 + 3L

3 +

2L ) L = p 2

As this sequence is one of positive terms, we have therefore a supremum of

p

2:

[12 marks]

2. (a) State the integral test and the alternating series test for inÖnite series. Given

1 ln n is continuous, positively valued and decreasing for

that the function f (n ) =

p
n

1

X

n = 3

p 1) ln n is convergent. Is the convergence of this

n

(

n

n 3, prove that the series

[10 marks]

SOLUTION: Integral Test: Let f (x ) be a continuous, decreasing, positive valued function for x 1: Then the inÖnite series

1

X f (n ) = f (1) + f (2) + f (3) + :::

n = 1

is convergent if and only if R

1 f (x ) dx is Önite, and is divergent if

1

b ! 1 Z b

Lim

1

f (x )dx = +1 :

1

1 ( 1) n+1 a n ;

SOLUTION: Alternating Series Test: Consider an alternating series

where a n 0 and a n+1 a n for all positive integers n: If lim 1 a n = 0; then the alternating series is convergent.

is

SOLUTION: Consider the series

decreasing for n 3; and

P

n =

n !

1

X

n

= 3

(

1)

n

1

n p ln n

p ln n : As the function f (n ) =

n

n

lim

! 1

1

n p ln n

= 0

3

by the alternating series test, the series is convergent. To determine whether the convergence is conditional or absolute, we use the integral test.

1

X

n = 3

(

1) n

n p ln n

=

1

X

n = 1

1

n p ln n

1 ln n is continuous, positively valued and decreasing for n 3; we can

n

p

As f (n ) =

use the integral test.

Z 1

3

1

x p ln x dx = Z

1

ln 3

1

p w dw = 2 p w

1

ln 3 = 1

Hence by the integral test,

1

X

n = 3

(

1) n

n p ln n

is divergent, meaning that the original series

1

X

n = 3

(b)

p 1) ln n is conditionally convergent.

n

(

n

Prove or disprove the following statements:

(i)

1

X

ja n j converges )

1

X a n converges.

 n = 1 n = 1 1 1

(ii)

X a n converges )

n = 1

[10 marks]

X ja n j converges.

n = 1

1

1

SOLUTION (i): It is true that

X ja n j converges )

n = 1

X a n converges. We will prove

n = 1

this as follows. Let us assume that

1

P

n =

1 a n is absolutely convergent. By deÖnition, this

1

implies that

is convergent, where we deÖne its nth partial sum to be

P

n =

1 ja n j is convergent. Its associated sequence of partial sums f n g ; n 1

n

= ja 1 j + ja 2 j + ::: ja n j :

Now let us deÖne the nth partial sum of the series

1

P

n = 1

a n to be

s n = a 1 + a 2 + ::: + a n

4

Here, the associated sequence of partial sums of

1; 2; 3; ::: Then clearly, n + p > n and

1

P

n =

1 a n is fs n g ; n 1: Now if p =

js n+ p s n j = =

ja n+1 + a n+2 + ::: + a n+ p j ja n+1 j + ja n+2 j + ::: + ja n+ p j n+ p n = j n+ p n j

(1)

(*Note: in (1) above, n+ p n = j n+ p n j since both quantities are positive). Hence we have that

(2)

But we know that f n g ; n 1 is a convergent sequence. Hence it is a Cauchy sequence, and for any > 0; 9 an n such that j n+ p n j < for p = 1; 2; 3; :::

Therefore, using (2) , we see that

js n+ p s n j j n+ p n j

js n+ p s n j < for p = 1; 2; 3; :::

Hence f S n g ; n 1 is also a Cauchy sequence, which means it is a convergent sequence.

It follows then that its associated inÖnite series

1

P

n =

1 a n is convergent.

SOLUTION (ii): It is false to say that

1

X a n converges )

n = 1

1

X

n = 1

ja n j converges. We

can prove this by counterexample.

test, but

1

X

n = 1

1

X

n = 1

(

1) n

n

=

1

X

1

n

n = 1

( 1) n

n

is convergent by the alternating series

the divergent harmonic series.

3. (a) Use the ratio test and the nth root test to derive two di§erent expressions for the

radius of convergence R of a power series

[6 marks]

1

X a n x n : Show all your working.

n = 1

SOLUTION: Applying the ratio test to

1

P

n =

0 c n (x a ) n ; we consider

lim

n ! 1

c n+1 (x a) n+1

c n (x a ) n

= jx a j lim

n ! 1

c

n+1

c

n

5

From the ratio test, we will have absolute convergence for

jx a j lim

n ! 1

c

n+1

c

n

< 1;

 i.e. for jx a j < where R = lim

n ! 1

c

n

1

c

n+1

c

n+1

c

n

c

n

c

n+1

= R

= lim

lim

n ! 1

n ! 1

SOLUTION: Applying the nth root test to

1

P

n =

0 c n (x a ) n ; we consider

lim 1 jc n (x a ) n j 1 =n = jx a j lim

n !

n ! 1

jc n j 1 =n

From the ratio test, we will have absolute convergence for

i.e. for

where

R =

jx a j lim 1 jc n j 1 =n < 1;

n !

jx a j <

1

lim jc n j 1 =n = R

n ! 1

1 jc n j 1 =n = radius of convergence.

lim

n ! 1

(b) Find the interval of convergence for the power series below. Show all your working and distinguish between conditional and absolute convergence in relevant cases.

1

X
(i)

n = 1

( 2) n (5x 3) 2 n

p n + 2

SOLUTION: Applying the ratio test, we have

lim

n ! 1

( 2) n+1 (5x 3) 2 n+2 p n + 3

( 2) n (5x 3) 2 n

p n + 2

6

=

2 j5x 3j 2 lim

n ! 1

= 2 (5x + 3) 2

p n + 2

p n + 3

Therefore we have absolute convergence, and therefore convergence for

When x =

1

p 2 +3

5

(5x 3) 2 <

1

2 )

p 1 2 < (5x 3) <

1

p

2

)

1

p 2 + 3

5

< x <

1

p 2 + 3

5

; the series becomes

X ( 2) n

1

n = 1

1

p 2 2 n

p n + 2

=

1

X

n = 1

(

1) n

p n + 2

By the alternating series test, this is convergent since

since lim

1

p n+2 = 0:

n !1

1

p n+2 >

1

p n+3 for all n 1; and

To test whether this convergence is conditional or absolute, consider

1

X

n = 1

(

1) n

p n + 2

=

1

X

n = 1

1

p n + 2

Using the limit comparison test with the divergent p series

lim

n

!1

1

p

n+2

1

p

n

n !1 r

n

n + 2 = 1 > 0

= lim

1

X

n = 1

1

n ; we have

p

Hence

at x =

When

1

X

1

p n+2 is divergent, and it follows that the series is conditionally convergent

n = 1 p 2 +3

1

5

1

2 +3

5

p

:

; the series becomes

X ( 2) n

1

n = 1

1

p 2 2 n

p n + 2

=

1

X

n = 1

(

1) n

p n + 2

which as we saw above is conditionally convergent.

(ii)

1

X

n = 1

n (2x ) 2 n

(n )!

7

SOLUTION: Using the ratio test, we have

lim

n !1

(n + 1) (2x ) 2 n+2 (n + 1)! n (2x ) 2 n

(n

)!

= (2x ) 2 lim

n !1

(n + 1) n ! n (n + 1)!

= 4x 2 lim

n !1

(n + 1) n ! n (n + 1) n ! = 0 < 1

Hence we have absolute convergence for all x 2 R :

[14 marks]

8